CAPACITY TO REDUCE TOTAL DISSOLVED SOLIDS (TDS) LEVELS IN THE IMPLEMENTATION OF ERGONOMIC WATER KNOCK FILTERS - Gempur Santoso; yoso wiyarno; poniman poniman (Tibuana, 2020)
Clean water is very important forlife. Provision of clean water is still a problemin Indonesia. 80% of Indonesia's populationstill consumes water that is not in accordancewith health standards. Whether ergonomicwater filters knock down for clean watersupply is the consumer's interest in waterusers. This ergonomic knock down water filterall parts are easily removed, carried easily,then reassembled where the location requireswater as long as there are waterways to getclean water. The design of this study iscomparative and experimental descriptive.Large sample of 30 people who use waterfilters. Place of Research in the IndustrialEngineering Ergonomics Laboratory, PGRIAdiBuana University Surabaya, Indonesia.Data is taken by observation, questionnaire,and experimental results. Data were analyzedusing descriptive percentages. The resultsshowed that 73.3% water filter material chosestainless steel. Ergonomic knock down waterfilters have the ability to reduce levels of totaldissolved solids (TDS) from 380 ppm to 156ppm, down 224 ppm (41%). Conclusions: 1)water filter users have the highest interest inchoosing filters made of stainless steel, areeasily installed and used ergonomically, andanti-oxidation does not cause corrosion; 2) thewater yield from ergonomic knock down waterfliter is 41% clearer than before filtering.Suggestion: To implement the QualityFunction Deployment of a knock down waterfilter, ergonomics are expected to be guided byanalytical analysis according to theconclusions above.